2022
DOI: 10.3390/ijerph19158894
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Risk Factors and Coping Strategies among Students in Asia Pacific during COVID-19 Pandemic—A Scoping Review

Abstract: The impact of COVID-19 has forced higher education institutes to go into lockdown in order to curb the situation. This sudden change caused students within the institutions to forgo traditional face to face classroom settings and to attend immediate online classes. This review aims to summarize the evidence of the social demographic mental health impacts of the COVID-19 pandemic on students in higher education institutes within the Asia Pacific region and identify the coping mechanisms adopted during these tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 104 publications
2
11
0
2
Order By: Relevance
“…For programs with limited support staff and budgets, careful preparation would be needed to tackle the technical and financial issues that will arise. Although a concern, the emergence of mental health issues in this study was similar to that found in several other recent studies, with slight differences in details depending on academic institution and region [ 14 , 17 , 18 , 19 , 20 , 21 ]. Interestingly, prior to such recent studies involving the influence of COVID-19 responses to the mental health of student bodies at academic institutions, much of the discussion focused on the benefits of online curricula.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For programs with limited support staff and budgets, careful preparation would be needed to tackle the technical and financial issues that will arise. Although a concern, the emergence of mental health issues in this study was similar to that found in several other recent studies, with slight differences in details depending on academic institution and region [ 14 , 17 , 18 , 19 , 20 , 21 ]. Interestingly, prior to such recent studies involving the influence of COVID-19 responses to the mental health of student bodies at academic institutions, much of the discussion focused on the benefits of online curricula.…”
Section: Discussionsupporting
confidence: 89%
“…The literature suggests Academic stakeholders are susceptible to impacts involving health, sociology, and achievement [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 31 , 32 , 33 , 34 , 35 ]. The generalization of Health as being the overall physical, mental, and emotional condition with regards to academic activities relevant to the individual.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies from across the globe measured depression, anxiety, and stress levels among university students [ 33 , 34 , 35 ]. However, very few of these studies measured depression at the time of home isolation and the COVID-19 outbreak.…”
Section: Literature Review: Covid-19 and The Mental Health And Psycho...mentioning
confidence: 99%
“…The outcomes of this research include the mental and psychological issues, such as the perception of stress and symptoms of depression and anxiety [ 5 , 6 ], suicidal ideation [ 7 , 8 , 9 ], post-traumatic stress disorder [ 10 ], and sleep disturbances, such as insomnia [ 11 , 12 ]. The pandemic has caused a reliance on mobile devices and extended screen-use time [ 13 ], leading to heightened levels of loneliness and social isolation [ 14 ], and increased social avoidance and feelings of distress [ 15 ]. In addition, it is associated with a decreased quality of life and lower subjective well-being [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%